Does the GeoGebra Application Affect Students' Motivation in Learning Mathematics? - AlAyyubi, IbnuImam; Noerzanah, Firda; Lidiawati, Lidiawati; Anggraeni, Ai Risma Sifa; Nurhikmah, Nurhikmah (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This study aims to improve students' learning motivation through the use of the GeoGebra learning application in overcoming challenges related to student interest in mathematics learning, particularly at SDN 074 Ayudia, Bandung City, with a population of all students and a sample of 31 students from class VA. This study uses a quantitative research method with an explanatory research approach. The sampling technique used is probability sampling with simple random sampling, while the instruments used are questionnaires and tests. The data analysis requirements testing includes normality testing using Kolmogorov-Smirnov and linearity testing, with the hypothesis tested through correlation and regression analysis using SPSS version 26. Based on the research results, it can be concluded that the GeoGebra application has a significant effect on students' mathematics learning motivation. The correlation analysis shows a very strong relationship between the two variables, with a correlation coefficient of 0.826, indicating that the use of the GeoGebra application can increase students' motivation in learning mathematics. This study also found that the GeoGebra application contributes 68.3% to the variation in students' learning motivation, showing that this technology has a significant impact on motivating students. This study implies that the GeoGebra application can be an effective learning tool to enhance students' motivation in mathematics learning.